Clinical Trials on Vagal Nerve Stimulation - Ozturk, Sait; Kok, Selman; Ergun, Ahmet Cemil (Nova Science Publishers, Inc., 2022)
Vagal nerve stimulation (VNS) surgery emerged in the 1980s as a treatment alternative for drug-resistant epilepsy (DRE) that is not amenable to resective surgery. The first VNS implant for epilepsy was performed in 1988. VNS therapy was approved in Europe in 1994 and by the United States Food and Drug Administration (FDA) in 1997. Since then, more than 130,000 people worldwide have used it. Long-term outcomes in epileptic adults and children show that the benefits from VNS persist over time, with responder rates of 50% (>50% seizure reduction). Follow-up for 5 years or more often shows a greater proportion of responders, at around 70%. Although VNS was not originally developed to treat depression, patients using VNS to treat epilepsy experienced mood improvement; thus, VNS indications were expanded to include the treatment of depression or some psychiatric disorders. Patients with chronic or recurrent major depressive disorder receiving VNS may have beneficial long-term outcomes. Recent studies of VNS in vivo systems have shown that it has anti-inflammatory properties which have led to more preclinical research aimed at expanding VNS treatment across a wider range of inflammatory disorders. Although the signaling pathway and mechanism by which VNS affects inflammation remain unknown, VNS has shown promising results in treating heart failure, obesity, chronic inflammatory disorders such as sepsis, lung injury, rheumatoid arthritis (RA), and diabetes. It is also being used to control pain in fibromyalgia and migraines. In this chapter, we provide an overview of the evidence and diverse applications of VNS in clinical practice, clinical trials, and preclinical research. © 2022 by Nova Science Publishers, Inc.